A EXPRESSÃO DO DIREITO NO ESPAÇO ESCOLAR: DIREITO EDUCACIONAL E ESTATUTO DA CRIANÇA E DO ADOLESCENTE NA PERSPECTIVA DA EDUCAÇÃO EM DIREITOS - Mattioli, Daniele Ditzel (2012)
This study focuses on the comprehension of how the Child and Adolescent Statute is dealt with in public schools in the Paraná Education System, in Ponta Grossa,regarding the paragraph 5th, article 32 of the Brazilian Guidelines and Bases for Education, which determines that the elementary school curriculum address the children and adolescents rights based on the Child and Adolescent Statute. It aims to verify how the Child and Adolescent Statute is materialized in the school life in public Schools in Paraná State, in the city of Ponta Grossa, in 2012. It also seeks: 1) to discuss the right to education in Brazil as seen by the education in rights; 2) to analyze the Child and Adolescent Statute in its relation with international instruments of chil‟ren's protection; 3) to recognize the Child and Adolescent Statute as a pedagogical tool for the education in values and development of children‟s and adolescents‟ autonomy. The first chapter addresses the public and subjective right to education and the Educational Law as the systematized juridical branch which gives the instruments to the participants involved in the education process. It also discusses the education in rights as a public policy enacted by the National Plan of Education in Human Rights, based on Benevides (2011), Bobbio (1992; 2000), and Dallari (2004) contributions. The second chapter develops an analysis of the international documents of defense of Human Rights of Children and Adolescents and the Child and Adolescent Statute based on Digiácomo (2010), Ishida (2011), and Comparato (2008) studies. The third chapter presents a study on education in the Brazilian Federal Constitution, based on the Brazilian Guidelines and Bases for Education and on the Child and Adolescent Statute, and the analysis of data collected. The methodology employed was explanatory research with a qualitative approach, developed based on the dialectic method from categories of the right to education and considering citizenship in childhood. For data collection, a questionnaire was applied to 39 (thirty-nine) State schools in Ponta Grossa-PR. The study allows to state that: a) the Children and Adolescent Statute is present in the school life, even if in disagreement with the current educational law, once it has been worked detached from the curriculum through lectures, debates, projects and in pedagogical meetings; b) education is recognized as a public subjective right and the education in rights as an educational process for the active citizenship development, based on the principle of human dignity; c) the approval of the Child and Adolescent Statute in the 1990s corresponds to the concretization of the Brazilian State Commitment in the international community with the defense of human rights of children and adolescents; d) there is some resistance of educational agents to recognize the Child and Adolescent Statute as a pedagogical instrument due to the lack of knowledge of its principles, along with the belief that it withdrew the authority of parents and teachers, as well, as the use of its institutions for the immediate solution of school problems, mainly regarding lack of discipline, in detriment of the children and adolescents‟ total protection which is one of its fundaments.